Transformational Leadership,Sustainable Leadership Development and Innovative Behavior among Primary School Teachers in Nairobi County ,Kenya. - Benard Abel Nyakundi (Pac University, 2025)
Creativity and innovative behavior among employees are some of the aspects that most institutions are struggling with. Most primary schools are faced with a myriad of challenges especially during transitions from one curriculum to another where teachers are supposed to get it right before the young learners at basic education levels are transitioned to secondary schools. Thus, this study aimed at exploring the implications of transformational leadership and sustainable leadership development on primary school teachers’ innovative behavior in 24 selected primary schools in Nairobi County, Kenya. The study was guided by transformational leadership theory with the following five objectives, namely exploring the implications of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration on primary school teachers’ innovative behavior in Nairobi County, Kenya respectfully. The fifth objective was to determine the moderating role of sustainable leadership development on the relationship between transformational leadership and primary school teachers’ innovative behavior in Nairobi County, Kenya. The study adopted descriptive research design using quantitative data which was guided by positivist epistemology research philosophy targeting a population 4278 primary school teachers in the 225 primary schools in Nairobi County of which a case study was conducted on 24 purposively selected primary schools. Purposive sampling was used to select the Head teacher, Deputy Head teacher, and senior teacher and class teachers for Grade 4 and Grade 6 while simple random sampling was used to identify 5 teachers adding up to 10 respondents from each of the 24 selected schools. The study collected quantitative data using closed-ended questionnaires that was analyzed using the statistical package for social sciences version 28 for descriptive, correlation, and regression analysis and was presented in tables based on the objectives of the study. The findings revealed that transformational leadership dimensions idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration had a collective effect on innovative behavior among primary school teachers. The model summary results showed an R-squared value of 0.525, indicating that these variables explained 52.5% of the variation in innovative behavior. The ANOVA results confirmed that the overall regression model was statistically significant (F = 52.597, p = 0.000), suggesting that transformational leadership significantly predicts innovative behavior. Regression coefficient results revealed that intellectual stimulation (β = 0.311, p = 0.002) and individualized consideration (β = 0.179, p = 0.049) had statistically significant positive effects on innovative behavior. However, idealized influence (β = 0.167, p = 0.084) and inspirational motivation (β = 0.088, p = 0.325) were not statistically significant predictors. The study concludes that transformational leadership significantly enhances teacher innovation when supported by intellectually stimulating and personalized leadership practices. In view of the findings, the study recommends that school leadership development programs should prioritize intellectual engagement and individualized support strategies to foster sustainable innovation among teachers.